Investigations on controlled transition development in a laminar separation bubble by means of LDA and PIV - Rist, U.; Lang, M.; Wagner, S. (Experiments in fluids, 2004)
When a laminar boundary layer separates because of an adverse streamwise pressure gradient, the flow is subject to increased instability with respect to small-amplitude disturbances. Laminaraturbulent transition occurs under a rapid three-dimensional (3D) development within the separated shear layer. When the following turbulent boundary layer reattaches, a laminar separation bubble is formed. To allow controlled measurements, a small-amplitude TollmienaSchlichting wave (TS wave) was introduced into the boundary layer without (case I) and with (case II) spanwise forcing of steady 3D disturbances. Combined application of laser-Doppler anemometry (LDA) and particle image velocimetry (PIV) demonstrates the suitability of both measurement techniques to capture the development of unsteady, periodic phenomena. The transition mechanism occurring in the flow field under consideration is discussed, and results obtained by controlled measurements are compared to direct numerical simulations (DNS) and predictions from linear stability theory (LST). Flow visualizations and stereoscopic PIV measurements give better insight into the 3D breakdown of the separated shear layer.